Memórias de alfabetizadoras do Programa Brasil Alfabetizado (2003-2010) - Silva, Thayana Priscila Domingos da (2016)
This research is developed within the Study and Research Group "History, Society and Education in Brazil" - Working Group / Paraíba. The main objective is to understand the memories of literacy teachers of the Literate Brazil Program, the city of João Pessoa - Paraíba, giving new meaning to their practices in order to subject visualize that has long stayed out of the versions of the official historiography, or occupied minimum and marginalized areas, although they have actively participated in the historical process. The scope makes it possible to increase knowledge about the educational setting with social and cultural relationship of Paraiba and Brazilian society in the XXI century. It characterized the historical period of the study (2003 - 2010), because it is the time of implantation and development of the Literate Brazil program by the government of Luis Inacio da Silva - Lula, of the Workers Party. The survey placed on the theoretical and methodological field of New Cultural History. Therefore, embarked to oral history through interviews as an essential way to listen to the characters, given that it enables you to set the historical-social universe of the performance of literacy teachers through the narrow lens of social micro-relations in spaces of Adult Literacy, through their speeches and statements, favoring new issues, problems and methodologies. So, three (3) literacy teachers participated in the interview that was designed from the perspective of oral history, pre-establishing a semi-structured script issues related to family background, everyday, training and educational activities. The study revealed the educational practices of women with a history of life dedicated to literacy, directly involved with the development of education, sometimes from very young. From the interviewees memories, narratives delineate their professional careers, highlighting the records of their experiences as historical subjects in the period in focus, such as literacy teachers Program Literate Brazil City João Pessoa / Paraíba. In this perspective, they point out the difficulties and anxieties they found in making education, in addition to knowledge and knowledge acquired during their training and experience. In operation with the Literate Brazil program, recall the living and the relationship with / the students / as, the actions within the program, such as the initial training, continuing education and class field, and the difficulties and limitations of working conditions and remuneration. So most of the time, these women and their educational practices are subject to anonymity and oblivion.